Phage-host co-evolution has led to distinct generalized transduction strategies - Wolput, S; Lood, C; Fillol-Salom, A; Casters, Y; Albasiony, A; Cenens, W; Vanoirbeek, K; Kerremans, A; Lavigne, R; Penadés, J; Aertsen, A (Oxford University Press, 2024)
Generalized transduction is pivotal in bacterial evolution but lacks comprehensive understanding regarding the facilitating features and variations among phages. We addressed this gap by sequencing and comparing the transducing particle content of three different Salmonella Typhimurium phages (i.e. Det7, ES18 and P22) that share a headful packaging mechanism that is typically initiated from a cognate pac site within the phage chromosome. This revealed substantial disparities in both the extent and content of transducing particles among these phages. While Det7 outperformed ES18 in terms of relative number of transducing particles, both phages contrasted with P22 in terms of content. In fact, we found evidence for the presence of conserved P22 pac-like sequences in the host chromosome that direct tremendously increased packaging and transduction frequencies of downstream regions by P22. More specifically, a ca. 561 kb host region between oppositely oriented pac-like sequences in the purF and minE loci was identified as highly packaged and transduced during both P22 prophage induction and lytic infection. Our findings underscore the evolution of phage transducing capacity towards attenuation, promiscuity or directionality, and suggest that pac-like sequences in the host chromosome could become selected as sites directing high frequency of transduction.